Associations between the consumption of red meat and processed meat and the incidence of colorectal cancer in Asia: a meta-analysis - Liao, Zhiyuan; Wu, Wenjiang; Xia, Shijun; Yu, Linchong; Xu, Zhigang; Li, Yue (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the correlation between the consumption of red meat and processed meat and the incidence of colorectal cancer (CRC) in Asia and provide a scientific basis for reducing the incidence of CRC.MethodsPubMed, Embase, Cochrane Library, and other databases were searched electronically to collect studies on the correlation between the consumption of red meat and processed meat and the incidence of CRC in Asia. After the quality evaluation of the Newcastle–Ottawa scale, meta-analyses of the selected studies were performed using RevMan 5.4.1. The odds ratio (OR) and 95% confidence interval (95% CI) were combined, and the heterogeneity among the included studies was analyzed via sensitivity analysis. I2 was used to evaluate the heterogeneity among the included studies.ResultsTwelve articles were included, which involved 13,292 and 12,544 cases in the case and control groups, respectively. The results of the meta-analysis revealed that in the study of the correlation between the consumption of red meat and the incidence of colon cancer, the combined OR was 2.14 (P < 0.00001); that for the consumption of red meat and the incidence of CRC, the OR was 1.77 (P = 0.006); that for the consumption of red meat and the incidence of rectal cancer, the OR was 2.42 (P = 0.0009); and that for the consumption of processed meat and the incidence of CRC, the combined OR was 1.51 (P > 0.05).ConclusionThe results suggest that red meat is a risk factor for the incidence of colon, colorectal, and rectal cancers. However, no significant correlation was found between the consumption of processed meat and the incidence of CRC.